MANAGEMENT OF Urochloa ruziziensis WITH GLYPHOSATE IN INTEGRATED SYSTEM WITH GLYPHOSATE-RESISTANT CORN - Corrêa, Gilmarcos de Carvalho; Pinto, Cássio Augusto; de Freitas, Evandro Macedo; Cunha Jr., Luís Carlos; Morgado, Cristiane Maria Ascari (REVISTA DE AGRICULTURA NEOTROPICAL, 2019)
This study aimed to evaluate the efficiency of the glyphosate doses in the suppression of Urochloa ruziziensis, to avoid the excessive competition of forage, intercropped with corn in an integrated crop-livestock system. The experiment was conducted in the experimental area of the Escola de Agronomia, of the Universidade Federal de Goiás with glyphosate-resistant corn (Zea mays L.) and Urochloa ruziziensis. The experimental design was randomized blocks with five treatments and four replications in a factorial scheme, with five herbicide doses x three evaluation periods. Treatments were control - non-sprayed, glyphosate herbicide at doses of 72, 144 and 288 g a.e. ha-1, and standard treatment of 8 g a.i. ha-1 of the nicosulfuron herbicide. The sowing was carried out in alternate rows of corn and forage with a spacing of 0.45 m between rows. The treatments were applied with corn at V6 vegetative stage and forage with 4-6 tillers, with evaluations at 7, 14, and 21 days after application. The dose of 72 g a.e. ha-1 of glyphosate, had no efficiency in forage suppression. The dose of 144 g a.e. ha-1 of glyphosate equaled the dose of 8 g a.i. ha-1 of nicosulfuron, which is the standard treatment in this intercropping system. Glyphosate at the dose of 288 g a.e. ha-1 caused the forage's death.